Aspects of hybridism in Joseph Conrad's Almayer's Folly and Heart of Darkness Aspectos de hibridismo em Almayer´s Folly e Heart of Darkness de Joseph Conrad - Solange Ribeiro de Oliveira (Ilha do Desterro)
In the light of concepts put forth by Cultural Criticism the essay discusses  Joseph Conrad´s novels Almayer´s Folly and Heart of Darkness as stagings of the conflicts inherent in the syncretic nature of all culture.  In the first novel,  Nina, the offspring of an interracial marriage, is analyzed   as a projection of the problems of  hybridism. The theme recurs in Heart of Darkness, in the figure of the “harlequin”, whose mixed ancestry  makes  him the butt of  continuous abuse. A fictional anticipation of Michel Serres´ allegorical harlequin , the half-caste proves close to three Conradian characters:  Nina, in Almayer´s Folly, and, in Heart of Darkness,  Kurtz and Marlow, the  narrator. Conrad´s two novels thus  nod to each other as mutually illuminating references, fictional premonitions of the key postcolonial category of hybridity.